2012
DOI: 10.1111/j.1476-5381.2012.01897.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional efficacy of adenosine A2A receptor agonists is positively correlated to their receptor residence time

Abstract: BACKGROUND AND PURPOSEThe adenosine A2A receptor belongs to the superfamily of GPCRs and is a promising therapeutic target. Traditionally, the discovery of novel agents for the A2A receptor has been guided by their affinity for the receptor. This parameter is determined under equilibrium conditions, largely ignoring the kinetic aspects of the ligand-receptor interaction. The aim of this study was to assess the binding kinetics of A2A receptor agonists and explore a possible relationship with their functional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
173
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(189 citation statements)
references
References 43 publications
9
173
2
1
Order By: Relevance
“…The initial experimental setup was based on previously published protocols for adherent cell lines (Guo et al, 2012;Scandroglio et al, 2010;Stallaert et al, 2012). While label-free assays are often deemed incompatible with suspension cells, some application examples exist for various label-free assays based on optical or impedance detection.…”
Section: Discussionmentioning
confidence: 99%
“…The initial experimental setup was based on previously published protocols for adherent cell lines (Guo et al, 2012;Scandroglio et al, 2010;Stallaert et al, 2012). While label-free assays are often deemed incompatible with suspension cells, some application examples exist for various label-free assays based on optical or impedance detection.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the difficulties mentioned above, the concept of residence time optimization of GPCR ligands has led to the development of antagonist drugs with long residence times such as tiotropium (Tautermann et al, 2013). Even for agonists, a positive correlation between agonist efficacy and residence time has been observed in the case of the M 3 acetylcholine receptor (Sykes et al, 2009) and at the adenosine A 2A receptor (Guo et al, 2012), although no such correlation was observed for the adenosine A 1 receptor (Louvel et al, 2014).…”
Section: State Of the Art: Currently Used Assaysmentioning
confidence: 98%
“…These time-dependent processes are an important consideration, as signaling assays require different incubations times and therefore may be differentially influenced by A 3 AR desensitization and/or internalization. Future studies will also assess the binding kinetics of structurally distinct A 3 AR agonists, as it is becoming appreciated that the agonist residence time can influence the efficacy and bias profile observed (Sykes et al, 2009;Guo et al, 2012;Klein Herenbrink, 2016).…”
Section: Discussionmentioning
confidence: 99%